Elucidación morfológico-estadística de las entidades del género Lepidobatrachus Budgett (Anura, Ceratophrynidae ), con consideraciones sobre la extensión del distrito chaqueño del dominio zoogeográfico subtropical - Reig, Osvaldo A. (1963)
Three populations of Lepidobatrachus are statistically analised as to twenty-five selected exosomatic, skeletal and myological characters. Twelve of these refer to the ratio between measurements, mostly of the skull. Comparison among the ranges of each variable (controlled by t and P calculations) demonstrates that each sample represents a different entity, one of which is L. asper Budgett, the other two representing new taxa. The position of Lepidobatrachus in the Leptodactyloid stock is discussed; according to Barrio’s ethological proposition this genus, Ceratophrys and Chacophrys are to be grouped in the Ceratophrynidae, remaining a matter to elucidate the inclusion of Odontophrynus, Stombus, Macrogenioglottus, Proceratophrys and Amblyphrynus. Lepidobatrachus, Ceratophys and Chacophrys seem to represent an apomorphic side branch. Finally the actual boundaris of the Chaco District are discussed. The distribution of many batracians supports an extension for the inclusion of semi-arid regions in the provinces La Rioja, San Juan, Mendoza, San Luis and Córdoba, which coincides with Morello’s “Quebracho Blanco District” based on geobotanical evidence.